Pledging movable property subject to registration while it remains in the possession of the mortgagor - عمر, سامان فوزي (Sulaimani Journal for Humanities, 2019)
This study deals with the mortgaging of immovable property subject to registration with remaining in the hands of mortgagor, and this hasn’t been a subject to Iraqi Civil Law, which divided the mortgage into two parts: the insurance mortgage that is applied on property only and possessory mortgage, which can be achieved only by transferring the possession of mortgaged from the mortgagor to the mortgagee in the hand of justice. Although the Iraqi legislator and through some specific laws tried to cope with the economical and credit developments and allowed to mortgage some movables properties that are subjective to registration such as ships, machines with the remain of its possession of the mortgagor, but he/she kept silent on some other private movables in the same way, such as cars and vehicles. Thus, we tried in this research to find general provisions to mortgage the movables subject to registration, depending on the Iraqi legislator to amend the Civil Code to develop some general provisions for this type of mortgage as some other countries did. We also have proposed amending the Iraqi Traffic Law to allow the registration od cars and other vehicles, while maintaining their possession with the owners, to achieve the objective insurance, which is the mortgagor credit and maintain the protection of the mortgagee.